EVALUATION OF THE PREVALENCE MYCOPLASMA GALLISEPTICUM IN BROILER FARMS IN SAMARRA CITY. - A.M. H. Aljoburi, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to evaluate the extent of the spread for  Mycoplasma gallisepticum  in the broiler chicken flocks of  the Samarra  city. 202 samples were collected from eight meat chicken fields in the city of Samarra for the period from September to December 2022, as these samples showed respiratory symptoms. The collected specimens were dissected in order to obtain both the trachea and the air sacs; After isolating the causative agent on Pleuropneumonia - like organisms (PPLOs) medium, mycoplasma infection reached 32.2%. The result appeared in the form of colonies with a shape similar to that of a “fried egg.” The rates of mycoplasma infection at culture for each of the trachea were (41.1%), while in contrast to the air sac samples, which amounted to (22.1%). Polymerase Chain Reaction (PCR) results for the 16S rRNA gene also showed a positive result for Mycoplasma gallisepticum. The results were also disturbed by the appearance of respiratory signs, such as coughing and sneezing, along with the presence of ocular and nasal secretions. It was also noted that pathological changes were recorded in both the trachea and air sacs, represented by congestion of these organs.